História em quadrinhos digital como estratégia de desenvolvimento da escrita em inglês - D'Ambrosio, Izabel Silva Souza (2017)
The aim of the present research was to understand the effectiveness of the written production through the Comics strategy (HQ) by digital means, focusing on the written production process through the software HagáQuê in the discipline of English. This dissertation appropriated the use of Digital Information and Communication Technologies to facilitate the process of textual production in the English Language and serve as an enriching vehicle in the process of teaching and learning. The discussions were based on writing production, teaching English and Digital Information and Communication Technologies. Considering this scenario, we discussed the new centrality of teaching English in Brazilian education and briefly discussed English as an additional language. As a theoretical contribution of this section, Jordão (2014), Rocha and Maciel (2015) were brought in. In sequence, questions about socio-interactionist work and autonomy, which contribute to the learning process, were based on Vygotsky (2008) and Freire (2016). The production of writing in English teaching was delt with (BROWN, 1994, 2000; KOCH, 2014; KAPLAN, 1996) supported by Digital Information and Communication Technologies (PRENSKY, 2007, 2012; GOMES, 2005, 2010; SCHNEIDER, 2002, 2012; LÉVY, 1996, 2003). Then, the Comics were explored with an account of its evolution (ANSELMO, 1975; RAMOS, 2010; RAMA, 2014; VERGUEIRO, 2014), its acceptance and importance in teaching, as well as its hybrid profile and its textual and multimodal genre (MARCHUSCHI, 2002, 2008, 2010; CANCLINI, 2016; KRESS, 2001, 2003; BARTON, 2015). Regarding the methodology (LÜDKE, ANDRE, 1986; MINAYO, 1995; BRANDÃO, 2006), the research was characterized as qualitative, based on the participant research and using as instruments of data collection, participant observation, interview and the questionnaire. For the data collection, the production of the Comics elaborated by the subjects participating in the research were also part of the study, in order to verify if there was a re-signification against the writing process with the experience through Comics, using HagáQuê software.